2013
DOI: 10.3109/07357907.2013.830737
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Breast and Abdominal Adipose Tissue Mesenchymal Stromal/Stem Cells in Support of Proliferation of Breast Cancer Cells

Abstract: In this study, we compared MSCs from breast and abdominal tissue in terms of their expression of genes deemed important in the support of breast cancer growth and their effect on gene profile of macrophages after coculture. In addition, we investigated the role of MSCs, alone or in combination with macrophages, on proliferation of breast cancer cell lines. Our results show that MSCs derived from breast and abdominal adipose tissues have a comparable gene expression profile, have similar effect on gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…Kim et al . [ 42 ] showed that MSCs increased proliferation of the MCF-7 and MDA-MB-231 cell lines. Fierro et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al . [ 42 ] showed that MSCs increased proliferation of the MCF-7 and MDA-MB-231 cell lines. Fierro et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to a recent report by Yang et al, which found only minimal expression of CD34 in normal breast-derived ADSCs [ 48 ]. Nevertheless, ADSCs from abdominal and normal breast fat share similar genetic profiles [ 59 ]. Moreover, reports of ADSCs isolated from primary breast cancer tissue have been published [ 50 , 60 62 ].…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%
“…Published reports, showing interaction between MSCs and cancer cells with subsequent promotion of their metastatic potential, call for further elucidation of these processes [6]. Despite the minor differences between studied MSC populations, similarities between bone marrow and adipose tissue-derived MSCs [22] and breast and abdominal-derived adipose tissues MSCs [23] have been demonstrated. Based on previously published results [7], we used a similar approach for EMT induction using MSC-CM in the SK-BR-3 cell line.…”
Section: Resultsmentioning
confidence: 99%